A IDENTIDADE LATINO-AMERICANA NA LITERATURA PÓSMODERNA: As múltiplas confessionalidades no limiar da nação - Barberena, Ricardo Araújo (Organon, 2012)
this essay aims to address the problem of identitary movements of a Latin- American cultural landscape permeated by plural processes of symbolic and affective affiliation. In this sense, the past decade has been especially significant for the dissemination of texts marked by marginal subjects, obstructed by a migrating and crossing be/being. Among the many works that support these multiple confessions and memorials of the I, we will underscore texts such as Paulo Lins’s Cidade de Deus, and César Aira’s As Noites de Flores.